1997
DOI: 10.1089/hum.1997.8.10-1207
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Responses to Proteins Encoded by Heterologous Transgenes TransferredIn Vivoby Adenoviral Vectors

Abstract: Although replication-deficient adenovirus (Ad) vectors are efficient vehicles for in vivo gene transfer, persistence of expression of the Ad genome is limited in immunocompetent hosts by cellular immunity directed against the gene product of the vector. While most attention has been focused on cytotoxic T lymphocytes (CTL) directed against the low-level early and late Ad gene expression in the Ad vector-infected target cells, significant cellular immunity is likely also directed against the product of heterolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…[1][2][3][4][5] However, recent studies have demonstrated that the replication defect in E1-deleted adenoviruses could be overcome in cultured cells at high multiplicities of infection (MOI) 6,7 and that the early and late viral gene products can be expressed independently of E1a function following adenovirus-mediated gene transfer in vivo. [8][9][10] The expressed viral genes may elicit a host immune response in the transduced cells and lead to toxicity, 11,12 limit the duration of transgene expression, [13][14][15][16] and consequently hinder the application of these vectors for human gene therapy. To overcome these drawbacks, further modifications have been targeted to the E4 and E2 regions of adenovirus, which are critical for viral DNA synthesis and late gene production, to diminish the residual DNA replication of viral vectors and reduce their potential for viral gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, recent studies have demonstrated that the replication defect in E1-deleted adenoviruses could be overcome in cultured cells at high multiplicities of infection (MOI) 6,7 and that the early and late viral gene products can be expressed independently of E1a function following adenovirus-mediated gene transfer in vivo. [8][9][10] The expressed viral genes may elicit a host immune response in the transduced cells and lead to toxicity, 11,12 limit the duration of transgene expression, [13][14][15][16] and consequently hinder the application of these vectors for human gene therapy. To overcome these drawbacks, further modifications have been targeted to the E4 and E2 regions of adenovirus, which are critical for viral DNA synthesis and late gene production, to diminish the residual DNA replication of viral vectors and reduce their potential for viral gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…76 -78 The expression of viral proteins and transgene products in Ad vector-transduced cells can stimulate destructive cellular immune responses, which leads to the coordinate loss of transgene expression and to the development of inflammation. Support for this observation has been derived from experiments performed in the nonhuman primate lung, 79 mouse lung, 80 liver, 71,81 spleen, 82 and cotton rat lung. 83 Ad vector-induced cellular immune responses clearly require redesign of the Ad vectors to eliminate the sources of the problem, although it was demonstrated that Ad vector-infected cells could escape Ad antigen (Ag)-specific cytotoxic T lymphocyte (CTL) killing in vivo.…”
Section: Concerns Of E1-substituted Ad Vectorsmentioning
confidence: 92%
“…Mice were sacrificed at 12 days after vector delivery, and splenic mononuclear cells were isolated as described previously. 45 Briefly, spleens harvested from each group were minced and ground, sheared with a 19-gauge needle, and passed through a 200-m mesh to remove fibrous tissue. Live lymphocytes were separated from dead cells and red blood cells using FicollPaque (Pharmacia, Piscataway, NJ) density separation, washed, and resuspended in Dulbecco's modified Eagle's medium.…”
Section: Cytotoxic T-cell Activity After Adil12 and Adil2 Delivery Inmentioning
confidence: 99%